Budgeting and Budgetary Control are time consuming tasks for any organization: Examination of how the preparation, operation and implementation phases are carried out to the benefit and achievement of a successful organization - Kwadade-Cudjoe, Francis (Archives of Business Research, 2020)
Budgeting and Budgeting Control are tasks that every organization has to undertake to successfully manage the operation of the entity. These tasks are very important organizational activities which need time to prepare, operationalize and implement successfully. It is the objective of every organization to be successful by achieving its goals and attain competitive advantage. With the proper contribution from management, the organization should be able to arrive at an acceptable budget, which would enable the operational managers to monitor and control their spending for organizational success. In this situation, the managers’ acumen would be called upon to direct operational / functional activities within the organization so that every member would contribute his / her quota, to the execution of the budget. Once the implementation is successful and furthermore exhuming benefits, there is hope that the entire gamut of the organization would revel in its achievement for higher productivity. A successful organization is surely the cynosure of every director of the board! Budgeting and Budgeting Control are tasks that every organization has to undertake to successfully manage the operation of the entity. These tasks are very important organizational activities which need time to prepare, operationalize and implement successfully. It is the objective of every organization to be successful by achieving its goals and attain competitive advantage. With the proper contribution from management, the organization should be able to arrive at an acceptable budget, which would enable the operational managers to monitor and control their spending for organizational success. In this situation, the managers’ acumen would be called upon to direct operational / functional activities within the organization so that every member would contribute his / her quota, to the execution of the budget. Once the implementation is successful and furthermore exhuming benefits, there is hope that the entire gamut of the organization would revel in its achievement for higher productivity. A successful organization is surely the cynosure of every director of the board.